Sphingobacterium multivorum: case report and literature review - Barahona, F. (New Microbes New Infect, 2015)
We describe the case of a 67-year-old African American woman with multiple medical problems who presented with septic shock resulting from Sphingobacterium multivorum bacteraemia. S. multivorum, a Gram-negative bacillus, is ubiquitous in nature and is rarely involved in human infections. However, it is intrinsically resistant to many commonly administered antibiotics and can be a life-threatening microorganism.